Hyperbaric oxygen therapy promotes the improvement of neurological recovery in rats with traumatic brain injury associated with TrkB activation. Issue 4 (28th December 2018) - Dan, Qi‐Qin; Li, Ting‐Ting; Liu, Fei
Abstract : Background: Hyperbaric oxygen (HBO) therapy has been proven to promote restoration of nerve function after traumatic brain injury (TBI), but the molecular mechanism is unclear. Methods: In this study, Sprague‐Dawley (SD) rats were adopted. The rats were randomly divided into Sham operation group, TBI group and TBI with HBO therapy group. Then movement and balance function of animals were observed by neurological severity scores (NSS). TUNEL staining was also used to detect the neuronal apoptosis. RT‐PCR, immunohistochemistry (IHC) and western blot (WB) were employed to detect TrkB expression in the mRNA and protein level. Results: The NSS scores showed that TBI deteriorated the motor function at 3 days (d), 7 d and 14 d post operation and accelerated apoptosis in the hippocampus. HBO treatment significantly improved the neurological function and suppressed cell apoptosis which is associated with increased of level TrkB expression. Conclusion: We confirmed HBO therapy can promote neurological functional recovery in TBI rats involving TrkB signal pathway.